254 LYMPH NODE DISSECTION IN T1 AND T2 ESOPHAGEAL SQUAMOUS CELL CARCINOMA: MINIMALLY INVASIVE ESOPHAGECTOMY VERSUS OPEN SURGERY. (17th September 2021) - Teng, Xiao; Cao, Jinlin; Xu, Jinming; He, Cheng; Zhang, Chong; Ye, Peng; Hu, Jian
Abstract:  : Minimally invasive esophagectomy is increasingly performed for esophageal squamous carcinoma, with advantages of improved perioperative outcomes in comparison with open esophagectomy. Lymph node dissection is one of most important prognostic factors, in esophageal squamous cell carcinoma. It is still unknown whether MIE can meet the criteria of lymph node dissection in the mediastinum, especially in T1 and T2 esophageal cancer. Here, we compared the lymph node dissection between MIE and open surgery. Methods: We retrospectively reviewed the clinicopathological data from 147 patients who underwent open surgery and MIE for esophageal squamous cell carcinoma from December 2016 to January 2020. The clinicopathological data including age, gender, number of lymph node resected were analyzed. Results: 68 patients underwent MIE and 79 patients underwent open surgery. The number of harvested lymph node didn't differ between the open surgery group and MIE group (26 ± 11.9 vs 26 ± 13.4, respectively, p = 0.128). However, the number of resected lymph node in the low para-esophageal region was significantly higher in open surgery group (4.1 ± 3.9 vs 2.8 ± 2.6, respectively, p = 0.019). The number of resected lymph node in the upper mediastinal region was significantly higher in the MIE group in T1 and T2 patients (4.7 ± 3.8 vs 2.7 ± 2.9, respectively, p = 0.014). the difference was also noticed in the para-recurrent laryngeal lymph node regions (3.6 ± 2.9 vs 2.0 ± 2.3, respectively, p = 0.020). Conclusion: For stages T1 and T2 esophageal squamous cell carcinoma, the lymph node dissection by MIE was comparable to that by open surgery. However, the number of harvested lymph node in the upper mediastinal region was better in the MIE group, which may indicate a better outcome. There was no difference in the postoperative complications, hospital stay and overall survival rate.